Effects of Drainage Water Management in a Corn–Soy Rotation on Soil N2O and CH4 Fluxes - Jacob G. Hagedorn; Eric A. Davidson; Thomas R. Fisher; Rebecca J. Fox; Qiurui Zhu; Anne B. Gustafson; Erika Koontz; Mark S. Castro; James Lewis (Nitrogen, 2022)
Drainage water management (DWM), also known as controlled drainage, is a best management practice (BMP) deployed on drainage ditches with demonstrated success at reducing dissolved nitrogen export from agricultural fields. By slowing discharge from agricultural ditches, subsequent anaerobic soil conditions provide an environment for nitrate to be reduced via denitrification. Despite this success, incomplete denitrification might increase nitrous oxide (N2O) emissions and more reducing conditions might increase methanogenesis, resulting in increased methane (CH4) emissions. These two gases, N2O and CH4, are potent greenhouse gases (GHG) and N2O also depletes stratospheric ozone. This potential pollution swapping of nitrate reduction for GHG production could negatively impact the desirability of this BMP. We conducted three years of static chamber measurements of GHG emissions from the soil surface in farm plots with and without DWM in a corn–soybean rotation on the Delmarva Peninsula. We found that DWM raised the water table at the drainage ditch edge, but had no statistically significant effect on water-filled pore space in the field soil surface. Nor did we find a significant effect of DWM on GHG emissions. These findings are encouraging and suggest that, at least for this farm site, DWM can be used to remove nitrate without a significant tradeoff of increased GHG emissions.